The Electrical Characteristics of Medium Voltage Insulators Against Contaminants at Coastal Area - Yulistya Negara, I Made; Asfani, Dimas Anton; Fahmi, Daniar (International Journal of Integrated Engineering, 2021)
Insulators have an important role in an electrical distribution line. They has a role as a mechanical support and on electrical insulation that isolate the live line and dead part of the electrical poles. Environmental factors will affect the performance of the insulator. Every area where the isolator was installed has a unique characteristics, therefore the electrical characteristics of each insulator will be differ from an area to others area. This study investigated the electrical characteristics of the 20 kV insulator for some feeder that representing all regions in coastal area. Coastal area has four types of areas, namely industrial, household, city, and rural areas. The leakage current of sample of these four area were measured and the Non-Soluble Deposite Density (NSDD) of each sample were also measured. The results show that the industrial area had the highest leakage current value of 1.22 mA while the lowest leakage current was observed in the household area of 0.44 mA. These were also confirmed that the industrial area had the highest NSDD value of 0.2412 mg/cm2 and the lowest NSDD in household areas of 0.0228 mg/cm2 were observed. Moreover, It was also observed that the highest flashover voltages and insulation resistance were in rural areas of about 53.4 kV and 261.33 GÎ©, respectively and the lowest flashovers were in household areas of about 39.34 kV and 118.83 GÎ©, respectively.